Hambatan Kemampuan Pra Literasi pada Anak Usia Dini (Studi Kasus pada Anak Usia 5-6 Tahun di TK Cor Jesu Marsudirini) - Dwiyanti, Kristina; Rita Intan Anggraeni; Wantini (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the barriers to pre-literacy skills in early childhood and the strategies used by teachers to overcome these challenges. The study is based on the importance of pre-literacy as the foundation of reading and writing skills, which determines children’s readiness for the next stage of learning. This research employed a descriptive qualitative approach, involving observation, interviews, and document analysis with 13 research subjects, consisting of teachers and children aged 5–6 years at TK Cor Jesu Marsudirini. Data were analyzed using Miles and Huberman’s interactive analysis technique, which includes three main stages: data reduction, data display, and conclusion drawing/verification. Through this process, data from observations, interviews, and documentation were systematically processed to identify patterns of barriers and the strategies teachers used to enhance children’s pre-literacy skills. The findings indicate that several problems in children’s pre-literacy include limited vocabulary, lack of family support and encouragement, and inadequate educational media. By implementing play-based learning, using more engaging visual and audio media, and involving parents actively in home-based stimulation, teachers strive to address these issues. Therefore, improving children’s pre-literacy skills requires collaboration among teachers, families, and schools through creative, engaging, and contextual learning strategies.